Climate Risk in Intermediate Goods Trade: Impacts on China’s Fisheries Production - Shunxiang Yang; Zefang Liao; Yingli Zhang; Yuqing Ren; Hang Qu (Fishes)
Climate change, especially extreme weather events, has significantly heightened the vulnerability of fisheries production supply chains. This study firstly investigates the input-driven climate risks through intermediate goods trade and their indirect impacts on China’s fisheries sector and constructs the Climate Risk-Trade-Production Model (CRTPM). Key findings include: (1) The input-driven climate risk indicator for China’s fisheries sector has increased over the period 1995–2020, with Brazil, Canada, the United States, Japan, South Korea, and Russia as major contributors. (2) From 1995 to 2020, rising climate risk index in Brazil and Canada negatively affected China’s fisheries output, with a 1% increase in climate risk index resulting in production declines of 0.173% and 0.367%, respectively. (3) In contrast, a reduction in the climate risk index in the United States and Japan lowered intermediate goods prices, boosting China’s output by 0.934% and 0.172%, respectively, for every 1% decrease in the climate risk index. (4) Climate risk index in South Korea and Russia, while initially increasing, eventually stabilized, having minimal impact on China’s fisheries production. It is the importance of monitoring extreme weather events to mitigate the economic vulnerabilities of China’s fisheries.